Strategic Rhythms: Insights and Research Directions. (July 2023) - Zhang, Pengxiang; Priem, Richard; Wang, Donghan; Li, Sali
Strategic rhythms concern how managers intentionally organize strategic activities by mapping them to the time continuum in hopes of improving a firm's long-term prospects. We develop a clear conceptual scope for strategic rhythms research. We take stock of the research on: rhythms of repeated strategic activity (e.g., serial acquisitions); rhythms of multiple strategic activities (e.g., sequencing activities for innovation); and comparison of strategic rhythms (e.g., for the firm, its rivals, the environment). We synthesize this literature in an integrative framework explaining the antecedents, content, and outcomes of strategic rhythms. We identify firm-level and environmental constraints that limit managers' discretion in enacting strategic rhythms, and we demonstrate two pathways through which managers may loosen those constraints. Finally, we identify promising opportunities for future research and suggest empirical techniques that will likely be useful for studying strategic rhythms.